IMPLEMENTASI TOTAL QUALITY MANAGEMENT PADA LEMBAGA PENDIDIKAN - Muhammad Rouf (LPPM Institut Agama Islam Al-Hikmah Tuban, 2017)
School/madrasah as an educational institution is an institution that serves as an agent of change to solve the nation's problems. Therefore, in order to produce the quality of education, it is necessary to implement the concept of TQM (Total Quality Management) that in history has successfully led the business world in creating production quality best and can even exceed the satisfaction of customers’ standard. This study used a qualitative approach with methods of library research. The formulation of the problem involves understanding implementation of TQM, TQM in education, implementation of TQM principles in educational institutions, the pillars of TQM in educational institutions, measures the implementation of TQM in education and description of the failure in the implementation of TQM. The study results were obtained, among others; The first, implementation of total quality management (TQM) is an implementation or embodiment of a management concept that involves all components in the organization to jointly contribute to the organization's policies oriented to the improvement of product quality to customer satisfaction. Second, in educational institutions, implementation of TQM are used to improve administrative functions and operations, to manage the educational process as a whole, integrate TQM in the curriculum, the use of TQM in teaching methods in the classroom, the use of TQM for managing research and development activities. In addition, educators must be responsible for their duties proactively, they must develop a problem-solving process that makes sense and can identify and towards the main cause, capable of being the organization model and can measure what's working well and what is not, so that we will get a good system in institutional schools / madrasah. Third, in applying TQM, there are some principles that should be held, among others; focusing on consumers (users of educational services), broad involvement (teachers, staff, students, and community), their measurements, to understand education as a system, and their continuous improvement. Fourth, the five main pillars of TQM here are their products, relying on the process undertaken, the leader who moves in producing quality products, and a commitment among the leaders in the organization. Fifth, steps in implementing TQM in educational institutions include; the preparatory phase, the planning phase and the implementation phase. Sixth, the failure may occur in implementing TQM in educational institutions, if; there is a gap in the commitment of top management, one focus of attention, lack of adequate staff and support, relying solely training, the hope of obtaining results of a moment and force adopt a method that doesn’t comply with the requirement.